Why Are We Not on the Road to Save the Earth and Us? Indirect Drivers of the Anthropogenic Impacts on Environment - Sabo, Peter; Sabová, Ľudmila; Turisová, Ingrid; Plašienková, Zlatica (Studia Ecologiae et Bioethicae, 2024)
The growth of anthropogenic impacts on environment rapidly acelerated since 1950s and led to overshooting of several planetary ecological thresholds, decreasing the Earth´s ability to support our civilization. Even the concept of sustainability did not lead to recognition of necessary limits to this growth. These limits define the framework of our study on the roots of the current environmental crisis. Numerous studies have been devoted to environmental degradation, but analyses of its indirect driving forces are often fragmentary and confusing. We have attempted to provide a systemic assessment of three groups of indirect drivers by reflecting new physical ones and adding the paradigmatic drivers – such as the mechanical heritage and low reflection of life´s awesome complexity. A paradigm shift is required, as the current paradigm is incompatible with the reality of the Earth´s life support systems erosion. We also strived to contribute to much debated value-based category analysis. This underlines complexity of the driving forces of the crisis. Moreover, some absurd theories of how to come out of the crisis were mentioned. We stress the opportunity for Christians to put into practice the biblical messages to become caring stewards of nature in the God's image.